On the stability of the troposphere/lower stratosphere and its relationships with cirrus clouds and three mandatory levels over Buenos Aires - Yuchechen, Adrian E. (2016)
Fil: Yuchechen, Adrian E. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina